2014
DOI: 10.1186/s12888-014-0363-z
|View full text |Cite
|
Sign up to set email alerts
|

Early risk factors for adult bipolar disorder in adolescents with mood disorders: a 15-year follow-up of a community sample

Abstract: BackgroundWe aimed to outline the early risk factors for adult bipolar disorder (BPD) in adolescents with mood disorders.MethodsAdolescents (16–17 years old) with mood disorders (n = 287; 90 participants with hypomania spectrum episodes and 197 with major depressive disorder [MDD]) were identified from a community sample. Fifteen years later (at 30–33 years of age), mood episodes were assessed (n = 194). The risk of developing BPD (n = 22), compared with MDD (n = 104) or no mood episodes in adulthood (n = 68),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 117 publications
1
18
0
Order By: Relevance
“…OR=3.6 and OR=6.6)[55]. In this study, of the 64 adolescents with hypomania spectrum episodes during childhood, only 6 developed a hypomanic/manic episode as adults.…”
mentioning
confidence: 48%
See 1 more Smart Citation
“…OR=3.6 and OR=6.6)[55]. In this study, of the 64 adolescents with hypomania spectrum episodes during childhood, only 6 developed a hypomanic/manic episode as adults.…”
mentioning
confidence: 48%
“…Longitudinal studies conducted in an unselected community-based sample can facilitate the generalisation of findings. In the Dunedin (New-Zealand) birth cohort (N=922 children), [55].…”
Section: Studies In a Community-based Samplementioning
confidence: 99%
“…Future research is however needed to confirm this finding. Previous analyses of the same cohort have shown that a family history of bipolar disorder was a strong significant risk factor for bipolar disorder in adulthood [37]. The number of individuals in the data material with bipolar disorder in adulthood is however too small to disentangle relationships between parents’ bipolar disorder, parental separation, and the individual’s depression and bipolar disorder.…”
Section: Discussionmentioning
confidence: 98%
“…Although the German study of Tijssen et al excluded baseline lifetime cases of BD, it did not nd any new cases of BD over the ensuing 8 years, despite the presence of hypomanic symptoms in some subjects and the study focusing on emerging affective symptoms. The 15-year follow up in the Swedish study (Päären et al 2013(Päären et al , 2014 found only a small percentage of adolescents with "hypomania spectrum disorder" developed BD-I (3%) or BD-II (6%) by their early 30 s.…”
Section: Adolescent Hypomania Often Not Resulting In Adult Bipolar DImentioning
confidence: 98%
“…The majority of bipolar spectrum cases across the 19 studies were of adolescents and by self-report. The validity of these diagnoses is thrown into some question by two of the newer studies ( Päären et al 2013( Päären et al , 2014Tijssen et al 2010) that incorporated follow-up interviews some years later. Although the German study of Tijssen et al excluded baseline lifetime cases of BD, it did not nd any new cases of BD over the ensuing 8 years, despite the presence of hypomanic symptoms in some subjects and the study focusing on emerging affective symptoms.…”
Section: Adolescent Hypomania Often Not Resulting In Adult Bipolar DImentioning
confidence: 99%